2004
DOI: 10.1128/jvi.78.4.2082-2087.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Human Immunodeficiency Virus Type 1 Ribosomal Frameshifting Site Is an Invariant Sequence Determinant and an Important Target for Antiviral Therapy

Abstract: Human immunodeficiency virus type 1 (HIV-1) utilizes a distinctive form of gene regulation as part of its life cycle, termed programmed ؊1 ribosomal frameshifting, to produce the required ratio of the Gag and Gag-Pol polyproteins. We carried out a sequence comparison of 1,000 HIV-1 sequences at the slippery site (UUUUUUA) and found that the site is invariant, which is somewhat surprising for a virus known for its variability. This prompted us to prepare a series of mutations to examine their effect upon frames… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
74
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 28 publications
9
74
0
Order By: Relevance
“…Changes in PRF efficiency alter those ratios, inhibiting virion morphogenesis (9). In particular, retroviruses appear to be very susceptible to such changes (4,21,33,37). Thus, elucidation of the molecular mechanisms underlying PRF can aid in the rational design of antiviral therapeutics (reviewed in reference 8).…”
mentioning
confidence: 99%
“…Changes in PRF efficiency alter those ratios, inhibiting virion morphogenesis (9). In particular, retroviruses appear to be very susceptible to such changes (4,21,33,37). Thus, elucidation of the molecular mechanisms underlying PRF can aid in the rational design of antiviral therapeutics (reviewed in reference 8).…”
mentioning
confidence: 99%
“…The efficiency of this frameshifting event varies between 2% and 15% among different viruses, with the majority of elongating ribosomes terminating translation normally at a P1 stop codon (4)(5)(6). Although it is unknown to what extent the frameshifting efficiency in plant luteoviruses influences viral replication and infectivity, studies in the human retrovirus HIV-1, Moloney murine leukemia virus, and the yeast L-A double-stranded RNA virus reveal that an optimal level of frameshift stimulation is essential for maintaining high levels of virus infectivity and propagation (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The second helix is formed by the pairing of the slippery sequence itself and the third helix anchors the others in a discrete structural element. It is suggested that this three helix structure explains why mutating the slippery sequence eliminates frameshifting, as this prohibits base pairing in the second helix [10]. In this instance the incorporation of the mutagenic ana lysis notably improves the argument and highlights the importance of including complementary Priority PaPer evaluation | Stephenson & Lever approaches and comparison with other genomes in order to increase confidence when attributing functionality to structural elements.…”
Section: Highlighted Structural Elementsmentioning
confidence: 99%